Spectrum of reperfusion strategies and factors influencing the use of primary angioplasty in patients with acute myocardial infarction admitted to hospitals with the facilities to perform primary angioplasty. Issue 4 (1st October 1999) - Zahn, R; Schiele, R; Seidl, K; Hauptmann, K E; Voigtländer, T; Rupprecht, H-J; Gottwik, M; Glunz, H G; Senges, J
Abstract : OBJECTIVE: To determine the frequency of the use of primary angioplasty in patients with acute myocardial infarction and the factors influencing its indications in hospitals with the facilities to perform this treatment. DESIGN: Data from the maximal individual therapy in acute myocardial infarction (MITRA) trial were analysed, concerning the effects of the decisions of individual hospitals, the time of admission of patients, and the effects of patient characteristics on the selection of reperfusion treatment. PATIENTS: Between June 1994 and January 1997 eight hospitals treated 1532 patients with acute myocardial infarction. 418 (27.3%) were treated conservatively, 641 (41.8%) were treated using intravenous thrombolysis, 387 (25.3%) were treated using primary angioplasty, and 86 (5.6%) received a combination of thrombolysis and angioplasty. RESULTS: The proportion of patients treated with primary angioplasty varied from 1.8% to 57.7% among the eight hospitals. The use of primary angioplasty during non-office hours also showed wide variation, ranging from 20% to 54% between centres. The use of thrombolysis was comparatively evenly distributed during the non-office hours, ranging from 50–69%. Four hospitals with a primary angioplasty use rate > 30% showed no difference in the proportion of patients with contraindications for thrombolysis, high risk patients, or a combination of both, when compared with four hospitals with a lower rate of primary angioplasty use (98/322 (30.4%) v 19/65 (29.2%), respectively, p = 0.847). CONCLUSIONS: In hospitals with the facilities for performing primary angioplasty the most important factors influencing its use were the discretion of the individual hospital and the time of patient admission. Characteristics of patients did not influence the choice of reperfusion treatment